Remembrances of Colonel Ezequiel Apodaca: Between Canchas Blancas and ‘Singani’ as a National Liquor [Memoria del Coronel Ezequiel Apodaca: Entre Canchas Blancas y el Singani Como Bebida Nacional] - Lacoste, P (Arturo Prat University, 2021)
This article offers a critical analysis of the book Remembrances of Colonel Ezequiel Apodaca (1880), which was published in 2017 in a context of significant controversy. The main objective is to ascertain the authenticity of the text. We establish that the main part (diary of a Bolivian official) is plausible, but not a complementary text (written by Lino Morales), which appears to be false. We thus conclude that there is no evidence to support the thesis of Canchas Blancas as being an important battle. However, the authentic source does provide important contributions on other issues, such as agricultural-food heritage. For example, this document shows the origins of Singani which has become one of Bolivia’s national liquors, providing important historical background that contributes to our understanding of the evolution of Andean distilled liquors in South America. © The Authors.